PALEOGENE STRUCTURAL DEVELOPMENT OF SOUTH AMAN TROUGH, CENTRAL SUMATRA BASIN - Suwandi Utoro, Edi
South Aman Trough is located on the southern part of Central Sumatra Basin. Seismic 3D data confirm that this trough is a pull apart half graben trending N-S as a result of dextral strike-slip mechanism which developed during rifting period coincided with development of all troughs in Central Sumatra Basin. Evaluation result using Supercube CS South seismic data shows 2 main structure trends developed in Paleogene Pematang Group, those are normal faults trending N-S occurred at Eocene - Oligocene and dextral strike slip trending NNW-SSE occurred in the late syn-rift period. Paleogene Tectonostratigraphy of this trough can be subdivided into 5 sequences package sedimentation, those are: Pematang-1 Sequence (Rift Initiation), Pematang-2 Sequence (Early Syn-rift), Pematang-3 Sequence (Middle Syn-rift), Pematang-4 Sequence (Middle Syn-rift) and Pematang-5 Sequence (Late Syn-rift, SB 25.5 Ma). Through tectonostatigraphic study approach of this syn-rift basin can be reconstructed a rift architecture understanding which will be giving valuable information in identifying syn-rift basin development significantly controlled by faulting activity of border faults and related synthetic normal fault striking north-south and gently dipping toward to the east. This rift architecture reconstruction is done by observing developing structure, interpreting of depositional environment from isochrone map and well data and its termination pattern of seismic reflection. The result shows that there are various deposits developed during half graben development in the research area such as axial channel, alluvial fan, delta fan, hinge margin delta and axial margin delta deposits. Perhaps this rift architecture reconstruction study will be giving better understanding about structural setting and depositional environment of Paleogene Pematang Group so that a new model and concept can be developed and can be referred to be a reference in conducting geological study and further exploration activities to explore hydrocarbon potential of syn-rift deposit in Central Sumatra Basin